L’enseignement universitaire de théologie, les rapports Centre/Périphérie et les usages des sciences humaines et sociales - Odaci Luiz Coradini (Cahiers de la Recherche sur l'Education et les Savoirs)
This paper presents as its central theme the specific position of Theology professors in face of the ensemble of Human and Social Sciences and their uses, through the study of social backgrounds and the relations with the academic and religious field of Theology professors at the Catholic Church and the Evangelical Church of Lutheran Confession in Brazil. The main effects of this increase is the subordination of those areas to the needs and strategies of theological disputes. Another observed aspect is the trend of reinforcing the “third-world pole” in the religious field, and their cross-relation with political-ideological disputes in general.